DIFFERENCES BETWEEN BLACK AND WHITE AMERICAN ENGLISH: SLANG EXPRESSIONS - FIKRI MURTADHA; Meisuri Meisuri; Masitowarni Siregar (LINGUISTICA, 2020)
This study deals with the differences between Black English and White American English based on the slang expressions as found in 10 songs by black and white rappers taken from YouTube videos. The analysis shows that the 5 songs by white rappers contain 394 sentences as compared with those of black rappers which is 493 sentences. The slang expressions are identified based on the existing theory and then they are categorized into the semantic change and morphological process  or formation of the expressions. It was found that there were more slang expressions in the Black English (39.95%) as compared with that of the White English (25.88%).There are more morphological processes in the black American English (6 of 8 types) compared with those of white American English (4 out of 8 types). The missing processes in black American English are borrowing and compounding whereas in the white American English are acronym, borrowing, backformation and conversion. The major or dominant processes in white American English are clipping (43.24%) and invention (41.44%) whereas in the black American English are clipping (30.02%) and invention (22.31%). At first sight it is difficult to understand the contents of the songs without referring to the explanations on the background and cultural values of the singers. The slang expressions which include a word, a phrase or a sentence contain the themes about sex, drugs and racialism among the black people in the United States. It is suggested that students who wanted to broaden their knowledge about English and its varieties should learn more about Black English. Keywords: morphological process; rappers; semantic changes; slang expression